Characterization Of Myocardial Dysfunction in Patients with Arterial Hypertension (The Peerian Journal, 2024)
The article characterizes early myocardial dysfunction (DM) in patients with threshold arterial hypertension (AH) and 1st degree AH. The technique of high-amplitude reflected motion signals (VOSD) has a higher sensitivity for detecting initial dysfunction in the left ventricular myocardium compared with traditional echodoppler parameters. WOSD allows to determine the parameters of diagnostic significance for Ea(c), Aa(c), Ea(c)/Aa(c), Ea(c) and Aa(c) in the separation of healthy individuals and 1st degree AH patients with already appeared minimal left ventricular diastolic dysfunction.